(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Globalization has significantly influenced India’s economic landscape, shaping its policies, industries, and social fabric. While globalization has catalyzed economic growth and opened up global markets, its effects on poverty, unemployment, and inequality remain complex and multifaceted. This review article explores the dual nature of globalization’s impact on these socio-economic parameters, highlighting the challenges and opportunities it presents.